2022
DOI: 10.3390/app122312246
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Implementations of ARIA on ARM Processors and Graphics Processing Unit

Abstract: The ARIA block cipher algorithm is Korean standard, IETF standard (RFC 5794), and part of the TLS/SSL protocol. In this paper, we present the parallel implementation of ARIA block cipher on ARMv8 processors and GPU. The ARMv8 processor is the latest 64-bit ARM architecture and supports ASIMD for parallel implementations. With this feature, 4 and 16 parallel encryption blocks are implemented to optimize the substitution layer of ARIA block cipher using four different Sboxes. Compared to previous works, the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These hardware-based methods provide a high level of performance optimization and have been the subject of numerous studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23]. In the same vein of research, the ARIA algorithm has also been the focus of optimization studies using parallel implementation with ARMv8 processors and GPUs (Nvidia GTX 3060) [24], as well as performance optimization based on low-power embedded processors (8-bit AVR microcontrollers) [25]. These studies demonstrate the increasing interest in exploring a variety of hardware-based approaches for accelerating block cipher algorithms in cryptography.…”
Section: Related Workmentioning
confidence: 99%
“…These hardware-based methods provide a high level of performance optimization and have been the subject of numerous studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23]. In the same vein of research, the ARIA algorithm has also been the focus of optimization studies using parallel implementation with ARMv8 processors and GPUs (Nvidia GTX 3060) [24], as well as performance optimization based on low-power embedded processors (8-bit AVR microcontrollers) [25]. These studies demonstrate the increasing interest in exploring a variety of hardware-based approaches for accelerating block cipher algorithms in cryptography.…”
Section: Related Workmentioning
confidence: 99%
“…Eum et al [46] studied the ARIA block cipher algorithm on ARMv8 processors. They compared their work to other work in the literature and found that their results reveal 8.73x performance improvements using ARM processors.…”
mentioning
confidence: 99%